Correlation Between Visual Prostate Symptom Score and Uroflowmetry Parameters in Patients with Benign Enlargement of Prostate - Gupta, Dipesh Kumar; Gupta, Sharmila; Jha, Niraj (Journal of Nepalgunj Medical College, 2017)
Background: Benign enlargement of prostate (BEP) needs treatment based on evaluation of symptom scoring among which International prostate symptom score (IPSS) is the standard one but carries difficulty in completion of the form. A visual prostate symptom score (VPSS) can evaluate the symptom with similar efficacy in a larger population with lower education.Aim of the study: The study was aimed to evaluate the correlation of the VPSS with uroflowmetry parameters.Materials and Methods. Men provisionally diagnosed as BEP were requested to complete the IPSS and VPSS, consisting of pictograms to evaluate urinary frequency, nocturia, force of the stream and quality of life. The maximum (Qmax) and average urinary flow rate (Qave), voided volume (VV) and post-void residual (PVR) urine volumes were measured. Statistical analysis was performed using the chi square test and Spearman's tests.Results. The study included 45 men (mean age 66 years, range 50-78 yrs.), with median prostate weight of 40 gm. One fourth of the patients were illiterate. Majority of the patients could complete VPSS without physician's assistance (46%). With mean voided volume of 273 ml, mean Qmax and Qave were 10.8 and 5.7, respectively. There was significant negative correlation of VPSS with Qmax (r=-0.435, p=0.003) and negative correlation of IPSS with Qmax, though insignificant (r=-0.1.05, p=0.4). Respective components of IPSS and VPSS also correlated significantly.Conclusion: The VPSS is equivalent to the IPSS in terms of correlation with uroflowmetry parameters and can therefore be used instead of the IPSS to evaluate LUTS in men with benign enlargement of prostate.JNGMC Vol. 13 No. 2 December 2015, page: 2-5